2018
DOI: 10.1080/09638288.2018.1424957
|View full text |Cite
|
Sign up to set email alerts
|

The association between adverse childhood experiences and adult traumatic brain injury/concussion: a scoping review

Abstract: A positive association between adverse childhood experiences and traumatic brain injury occurrence was identified. The review highlights the importance of screening and treatment of adverse childhood experiences. Future research should extend to the general population and implications on injury recovery. Implications for rehabilitation Exposure to adverse childhood experiences is associated with increased risk of traumatic brain injury. Specific types of adverse childhood experiences associated with risk of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Furthermore, these adverse experiences may be accompanied by the dysfunction of cognitive functions resulting from brain injuries [119], such as abused and neglected children, victims of violent crime and assault, refugees, veterans, and minority groups. To support this notion, several studies have established a link between cognitive functions and traumatic brain injury [120,121]. Analogous to the neural plasticity that occurs in response to brain injury [10,[122][123][124], resilience can be viewed as the developmental process of an individual adapting after exposure to adverse events or traumatic experiences [125].…”
Section: Linking the Malleable Brain Resilient Mind And Adaptive Bementioning
confidence: 99%
“…Furthermore, these adverse experiences may be accompanied by the dysfunction of cognitive functions resulting from brain injuries [119], such as abused and neglected children, victims of violent crime and assault, refugees, veterans, and minority groups. To support this notion, several studies have established a link between cognitive functions and traumatic brain injury [120,121]. Analogous to the neural plasticity that occurs in response to brain injury [10,[122][123][124], resilience can be viewed as the developmental process of an individual adapting after exposure to adverse events or traumatic experiences [125].…”
Section: Linking the Malleable Brain Resilient Mind And Adaptive Bementioning
confidence: 99%
“…23 ACEs may represent a step along a pathway that increases risk for ABI, for instance, via neglect by a parent that could lead to drowning or a bicycle crash, physical abuse by a parent or intimate partner by strangulation and health risk behaviours, such as substance use, which may cause a stroke, drug overdose or heart attack/failure. Ma and colleagues 24 conducted a review of the existing literature between ACEs and subsequent TBI in adulthood and found a possible relationship between ACEs and TBI; however, the six studies included in the review were limited to incarcerated or homeless samples and individuals at high risk of or with mental illnesses. Individual studies and systematic reviews continue to reveal significant associations between ACEs and health conditions, further underscoring the need to prevent ACEs.…”
mentioning
confidence: 99%
“…For example, a recent study examined adults who experienced a childhood TBI in a Swedish birth cohort, comparing them to siblings who did not experience an injury 90 . Findings from this and similarly designed studies indicate that individuals who experience a childhood TBI have lower rates of enrollment in postsecondary education, are less likely to be employed or live independently, and are more likely to work in entry-level or low-skilled jobs when compared to those with other disabilities or individuals who have not experienced a TBI 19,[90][91][92][93][94][95][96] .…”
Section: Long-term Outcomes In Childrenmentioning
confidence: 99%